TREATMENT OF DEPRESSION IN CARDIOVASCULAR DISEASE. Issue 4 (4th January 2013) - Mavrides, Nicole; Nemeroff, Charles
<x xml:space="preserve">Abstract</x> Background and Objectives Depression in patients with Cardiovascular Disease (CVD) is extremely common, with a prevalence of 17–47%, and is associated with increased risk of morbidity and mortality. Treatment of depression has been hypothesized to reduce cardiac mortality. Pharmacologic and psychotherapeutic interventions have been studied and appear to be safe and in some studies effective in reducing depressive symptoms in patients with cardiac disease. The impact on cardiac outcomes remains unclear. This review briefly focuses on the prevalence of depression in patients with CVD, the physiological links between depression and CVD, and largely is concerned with the clinical trials that seek to demonstrate efficacy and safety of antidepressant medications and psychotherapy in this patient population. Methods PubMed and PsycINFO databases were searched through July 2012. Publications were included if they were in English, a review article, or a clinical trial in the CVD population with comorbid depression. The search was completed with key words of antidepressants, CVD, coronary artery syndrome, SSRIs, depression, treatment of depression, post‐MI (where MI is myocardial infarction), major depression, and cardiac disease. Trials were included if the patients were above the age of 18, both male and female genders, and had cardiac comorbidity. No trials were excluded. Results A total of 61 articles and/or book chapters were included. The majority were from North America and Europe. There were 7 clinical trials of tricyclic antidepressants (TCAs), one of TCAs and bupropion, and 10 trials of selective serotonin reuptake inhibitors (SSRIs). We also evaluated five trials involving psychotherapeutic techniques and/or collaborative care. Conclusions There is considerable evidence from randomized controlled clinical trials that antidepressants, especially SSRIs, are safe in the treatment of major depression in patients with CVD. Although efficacy has been demonstrated in some, but not all, trials for both antidepressants and certain psychotherapies, large, well‐powered trials are urgently needed. There are virtually no data available on predictors of antidepressant response in depressed patients with CVD. Whether successful treatment of depression is associated with a reduction in cardiac morbidity and mortality remains unknown.